Prevalence of microsporidiosis in human and cattle: Kadum, N. E. and Alwan, M. J. - E., Kadum N. (The Iraqi Journal of Veterinary Medicine, 2017)
In order to identify microsporidia and other fungi in stool and urine samples of human, and in fecal and milk samples of cattle, 100 stool samples with or without diarrhea and 50 urine samples, human fecal and urine samples were obtained from certain Baghdad hospitals and certain rural areas surroundings Baghdad city, in addition to 50 fecal and 56 milk samples of cattle apparently healthy were collected from Alshula Slaughter House and directly from anal of the animal field of College of Veterinary Medicine/ Baghdad University. All samples were collected during six months from 1/10/2014 to 1/4/2015. Thin films were formed and stained by Webers Modified Trichrom stain and Modified Trichrom-Ryan Blue stain. The results showed that (23%) 23 out of 100 stool samples of human were positive for Microsporidia spp. and (16%) 8 out of 50 urine samples of human were positive for this fungus. While the result revealed (18%) 9 out of 50 fecal samples and (7.14%) 4 out of 56 milk samples of cattle were positive for Microsporidia spp. The result also explained that (25.3%) 19 cases of patients suffering from diarrhea expressed Microsporidia spp. after the examination of 75 stool samples, while (16%) 4 persons without diarrhea showed positive Microspordia, through the examination of 25 stool samples. The study explains that the Enterocytozoon bieneusi is a common species associated with human infection and Encephalitozoon intestinalis is a common Microsporidia associated with cattle infection whereas Encephalitozoon cuniculi is rarely identified in human but recorded in cattle.